What Politics? Youth and Political Engagement in Africa - Oinas, Elina; Onodera, Henri; Suurpää, Leena (Youth in a Globalizing World, 2017)
What Politics? Youth and Political Engagement in Africa examines the diverse experiences of being young in today's Africa. It offers new perspectives to the roles and positions young people take to change their life conditions both within and beyond the formal political structures and institutions.